The â€œF Wordâ€ Among Bilingual Children in Their First Language - Rahayu, Puji; Setiawan, Slamet (Universitas Negeri Semarang, 2021)
A new phenomenon comes up early today that the F word or fuck has been becoming popular among children regardless of the setting. The study examines the childrenâ€™s perception towards the F word in two cities in East Java: Surabaya (a metropolitan city) and Jombang (a sub-urban city). To investigates F words' usage among fifty children eight â€“ fourteen years old in these two places, a descriptive qualitative method was employed by conducting interviews and observation. The result shows six perceptions through the F word: impolite word, an angry expression, a friendly word, a joke, and an offensive word. The way in which they acquire the F word varies, as does the purpose and the function of the F word as a wave of anger, sarcasm, conformity, solidarity, and frustration.